PROBLEMATIKA SERTIFIKASI HALAL PADA PRODUK INDUSTRI KERUPUK DI SURAU PINANG - Hidayatul Husna; Sulastri Caniago (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
This study examines the review of Law No. 33 of 2014 concerning Guaranteed Halal Products for Halal Certification of Crackers Industrial Products in Jorong Surau Pinang Nagari Ampang Gadang, Ampek Angkek District, Agam Regency. in Jorong Surau Pinang Nagari Ampang Gadang, Ampek Angkek District, Agam Regency, there is one Home Industry Producer that produces processed food, namely the manufacture of crackers whose packaging or brand includes a halal label, but does not comply with the official halal label from the MUI and also without going through certification halal that has been determined by the government. This research is a field research (field research). Data obtained through interviews and observations. After the collected data is processed by reading and understanding the text, then the data is narrated descriptively, the results are discussed with the theories put forward. This study found the obstacles experienced by home industry owners making crackers to carry out halal certification, namely the lack of understanding and knowledge about the process of doing halal certification. From the obstacles experienced by home industry owners for making crackers, Law number 33 of 2014 can accept the obstacles experienced by home industries because in its current implementation it is indeed from the competent authorities such as the MUI (Indonesian Ulema Council) lack of or almost no socialization to the public, especially industries such as food manufacturing, thus having an impact on home industries who do not know and understand that it is very important to carry out halal certification, especially for food products and also the absence of sanctions against law number 33 of 2014 article 4.